Tra banchi, quaderni e calamai: la storia materiale della scuola nelle immagini della Fototeca storica INDIRE - Vanni, Laura (Studi sulla Formazione/Open Journal of Education, 2016)
The essay will focus on school material history, analyzing the value of photography as a source, and presenting INDIRE photographic historic archive ("Fototeca storia INDIRE") as a precious collection of documentation regarding this field of research.